An online experiment on the influence of online user comments on attitudes toward a minority group - Stylianou, Stelios; Sofokleous, Rafael (My University, 2019)
In recent years, there is interest in examining the effects of user comments on online content consumers’ attitudes and perceptions. Building on theoretical foundations from social psychology and using an online experimental design, we investigated whether exposure to online comments attached to news content affects attitudes toward refugees. We recruited students from a public university in the Mediterranean region and, after administering a printed pretest on their attitudes toward refugees, we assigned them into three groups: one that read a series of positive comments about refugees (positive experimental group), one that read a series of negative comments about refugees (negative experimental group) and one that did not read comments (control group). The comments and a neutral reference news video were communicated to the participants via email during a five-day period after the pretest. After the implementation of the experimental stimuli, we administered a modified version of the pretest as a posttest. We found that exposure to positive comments reduced prejudice and that the intensity of prior prejudice was positively associated with the magnitude of prejudice reduction. Exposure to negative comments did not affect prejudice. A repeat posttest, administered one week after the posttest, showed stability of the observed attitude change.
Keywords: Social influence; Online experiment; Prejudice; Attitudes; Online news; Online user comments; Social norms